Origins of Bistability and Na Ion Mobility Difference in P2‐ and O3‐Na2/3Fe2/3Mn1/3O2 Cathode Polymorphs. Issue 1 (5th September 2016) - Katcho, Nebil A.; Carrasco, Javier; Saurel, Damien; Gonzalo, Elena; Han, Man; Aguesse, Frederic; Rojo, Teofilo
Abstract : Transition metal layered oxides are promising cathode materials for sodium‐ion batteries. Phase transitions involving different stacking sequences of the oxide layers often plague the electrochemistry of these materials during cycling, which strongly impacts in their electrochemical performance. However, the underlying mechanisms of these processes remain elusive. Interestingly, P2‐ and O3‐Na2/3 Fe2/3 Mn1/3 O2 phases are the first transition metal layered oxide polymorphs that have been synthesized with exactly the same composition. This offers unprecedented access to the study of bistability in these systems as well as isolates the effect of local structure on Na ion mobility. Here, first‐principles calculations and experiments are combined to unveil the physical origin of such bistability and identify important differences in Na ion diffusion between these two phases. It has been found that electrostatic interactions between oxide layers control the bistable nature of P2 and O3 phases. It is also put forward that the interlayer distance between oxide layers may be a useful descriptor to rationalize the relative stability of other P and O phases in general. Furthermore, this study tracks down to the molecular level the differences regarding Na ion mobility in P2‐ and O3‐Na2/3 Fe2/3 Mn1/3 O2 by computing activation energies and estimating diffusion coefficients. Abstract : P2‐ and O3‐Na2/3 Fe2/3 Mn1/3 O2 cathode materials for sodium‐ion batteries are the first transition metal layered oxide polymorphs that have been synthesized with exactly the same composition. First‐principles calculations and experiments are combined to unveil the physical origin of such bistability. Additionally, important differences in sodium ion diffusion between these two phases are identified.